Impacts of Aging and Blackcurrant Supplementation on the Gut Microbiome Profile of Female Mice (P20-031-19) - Lee, Sang Gil (Curr Dev Nutr, 2019)
OBJECTIVES: Blackcurrant, an anthocyanin-rich berry, has multiple health benefits. The purpose of this study was to examine the impacts of blackcurrant supplementation and aging on gut bacterial communities in female mice. METHODS: Three-month and 18-month old female mice were provided standard chow diets with or without anthocyanin-rich blackcurrant extract (BC) (1% w/w) for four months. Upon study completion, fecal samples were collected directly from the animals’ colons. Microbiome DNA was extracted from the fecal samples and the V3-V4 regions of their 16S rRNA gene were amplified and sequenced using RESULTS: Taxonomic analysis showed a significantly decrease in alpha diversity in aged female mice, compared to young counterparts. BC consumption did not alter the alpha diversity in either young or aged mice compared to control diets. For beta diversity, we observed the clustering was associated with age but not diet. The phylogenic abundance analysis showed that the relative abundance of several phyla, including Firmicutes, Bacteroidetes, Cyanobacteria, Proteobacteria, and Tenericutes was higher in aged compared to young mice. Among them, the abundance of Firmicutes was downregulated by BC in the young but not the aged mice. The abundance of Bacteroidetes was increased by BC in both the young and the aged groups. Noticeably, Verrucomicrobia was the only phylum whose relative abundance was upregulated in the aged female mice compared to the young mice. Meanwhile, its relative abundance in the aged group was suppressed by BC. Interestingly, Desulfovibrio, which is the most representative sulfate-reducing genus, was detectable only in young female mice, and BC increased its relative abundance. CONCLUSIONS: Our results characterized the gut microbiome compositions in young and aged female mice, and indicated that the gut microbiome of young and aged female mice responded differently to four month BC administration. Through additional research, the microbial alterations observed in this study should be further investigated to inform our understanding of the effect of BC on the gut microbiome, the possible health benefits related to these changes, and the differing effects of BC supplementation across populations. FUNDING SOURCES: This study was supported by the USDA NIFA Seed Grant (#2016-67018-24492) and the University of Connecticut Foundation Esperance Funds to Dr. Ock K. Chun. We thank the National Institute on Aging for providing aged mice for the project and Just the Berries Ltd. for providing the blackcurrant extract.